Analisis Yuridis Distribusi NFT Bermuatan Pelanggaran Data Pribadi Berdasarkan Undang-Undang Nomor 27 Tahun 2022 Tentang Pelindungan Data Pribadi - Nafisah Muthmainnah; Danrivanto Budhijanto; Tasya Safiranita (Publikasi Indonesia, 2023)
Digital transformation in the economic sector has challenged legal and regulatory capabilities. The euphoria of the Indonesian people over the presence of the Non-Fungible Token (NFT), especially on the OpenSea platform, has caused a violation of privacy. Therefore, this research examines the basis for processing the personal data of OpenSea and their accountability for efforts to protect personal data in a descriptive-analytical specification with a normative juridical approach originating from library materials or secondary data. The results of the research show that the basis for processing data is not in line with Law Number 27 of 2022 concerning the Protection of Personal Data, and OpenSea may be subject to administrative sanctions for the distribution of NFTs that are contented with personal data violations in its electronic system. Meanwhile, this research aims to contribute ideas and references for legal knowledge development; input to the government to reinforce preventive and repressive efforts on internet security; referral of personal data controllers in improving the quality of electronic systems; and information for the public to wisely utilize technology.